Ultra Wideband Impulse Radio Superregenerative Reception - Moncunill-Geniz, F. Xavier; Palà-Schönwälder, Pere; Bonet-Dalmau, Jordi; López, Francisco Del Aguila; Giralt-Mas, Rosa (IntechOpen, 2011)
None